2022
DOI: 10.1016/j.csbj.2022.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast is a dual-purpose inhibitor of SARS-CoV-2 infection and virus-induced IL-6 expression identified by structure-based drug repurposing

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
1
9
0
3
Order By: Relevance
“…Молекулярно-динамическое моделирование показало, что монтелукаст будет нарушать структуру рецепторсвязывающего фрагмента S белка RBD SARS-CoV-2, соединяясь с областью, близкой к RBD (ARG-331, ASN-368, VAL-369, THR-404, SER-488) [33].…”
Section: противовирусные эффекты монтелукастаunclassified
See 2 more Smart Citations
“…Молекулярно-динамическое моделирование показало, что монтелукаст будет нарушать структуру рецепторсвязывающего фрагмента S белка RBD SARS-CoV-2, соединяясь с областью, близкой к RBD (ARG-331, ASN-368, VAL-369, THR-404, SER-488) [33].…”
Section: противовирусные эффекты монтелукастаunclassified
“…Функциональная значимость монтелукаста против инфекции SARS-CoV-2 показана ингибированием инфекции in vitro. Монтелукаст предотвращал заражение SARS-CoV-2 (WT, бета-вариант, но не альфа-вариант) при высоких значениях IC50 выше 137,3 мкМ [33]. Поскольку монтелукаст действует как антагонист цистеиниллейкотриеновых рецепторов, предотвращая активацию клеток и выработку медиаторов воспаления, таких как IL-6, исследователи пришли к выводу о том, что монтелукаст может также снижать SARS-CoV-2-индуцированную экспрессию цитокинов иммунными клетками.…”
Section: противовирусные эффекты монтелукастаunclassified
See 1 more Smart Citation
“…A computational simulation predicts that montelukast may bind S protein to disturb the RBD domain. 418 Montelukast sodium hydrate binds with the C-terminus domain of SARS-CoV-2 NSP1 protein to restore host protein synthesis, which is suppressed by NSP1. 419 , 420 …”
Section: Introductionmentioning
confidence: 99%
“…Montelukast, a leukotriene receptor antagonist safely used in asthma patients for many years, has the potential to inhibit SARS-CoV-2 and MERS-CoV infection [ 17 , 18 , 19 ] and has the ability to inhibit Zika virus infection by disrupting its integrity [ 20 ]. In this study, we found that montelukast could also effectively inhibit the infection of HCoV-OC43 by screening FDA-approved drugs.…”
Section: Introductionmentioning
confidence: 99%